Contraceptive trends in an industrial belt of central India: a study in ESIC Model hospital over three years - Mukherjee, Shubhra; Bhattacharjee, Somen; Sodhiya, Hemlata (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: India was the first country to adopt a population policy and launch family planning program in 1952. Contraceptive usage has tripled in last 40 years. Although the national fertility rate has dropped significantly, the total fertility rate of MP is still at 2.0. The unmet need of contraception was evaluated at 9 % (NHFS 4), dropped down to 5.2 % in urban areas (NHFS 5, phase 1). The focus is mainly on birth limitation. Methods: The study was conducted in department of obstetrics and gynecology in ESIC Model hospital, Indore. Period of study was from January 2019 to December 2021. Study population comprised of 300 married non-pregnant women. Data was divided into three categories-traditional methods, temporary modern methods and terminal methods. Study population was divided into five groups-number of living children, religion, education, residence, income. Results: 48% of study population had two or more living children. Maximum women belonged to Hinduism (62.5%) followed by Islam (26.3%). Majority of women belonged to urban residence (55.33%). Traditional method of contraception usage was overall low (5-6.7%). The most popular method was the terminal method (69-75 %) followed by temporary method (20-23%). No male sterilization done in this period. Conclusions: Female sterilization accounts for two thirds of all contraceptive use. The usage of modern methods is limited. Male sterilization is soon going to be a thing of past. The burden of contraception still falls on women. The focus should shift from birth limitation to birth spacing.